Particle Swarm Optimization Technique for Solving Economic Emission Dispatch Problems - Vennila, H.; Deva Prakash, T.Ruban (Procedia engineering, 2012)
This paper presents a new approach to Economic Emission Dispatch (EED) with the consideration of five thermal generating units using Particle Swarm Particle Swarm Optimization Technique (PSO). To reduce SO2 and NOX emission, there are various methods, such as installing post-combustion cleaning system, switching to fuels with low emission potential and dispatching load with consideration of an environmental issue. Among them, formulation of environmental economic dispatch is preferred in operation of the existing systems because it is easy to implement and requires minimal additional costs. Economic emission dispatch is subject to a number of inequality and equality constraints. Many of these techniques suffer from natural complexity and converge slowly. The PSO method has been applied successfully meeting all the constraints and compared with the classical optimization technique. In this project the results of PSO are compared with the results of conventional method and proved to be better